Hepatology Textbook and Atlas - Kuntz, Erwin; Kuntz, Hans-Dieter (Springer Berlin Heidelberg : Imprint: Springer, 2008)
Instructive - Attractive - Unique Textbook - Completely revised, updated and enlarged - Close and continuous relation between pathomorphology, function and clinic - Further improvements in content, systematology, didactics and colour design - Numerous, sometimes unusual, but clinically proved suggestions ("tips and tricks") resulting from the author's practical experience Atlas - A total number of 530 figures in colour and 320 tables in colour - an hepatological atlas which is unique in form, extent and presentation Manual - About 7,000 quoted publications - Some 1,500 cited first-descriptors of therapy procedures, methods, medical techniques and invasive measures - A comprehensive index containing more than 3,000 terms and about 12,000 cited reference pages - Register of abbreviations + ALL figures and tables on CD-ROM This textbook is escorted along its way by a foreword from: - Ch. S. Lieber (New York, USA) - 1st edition - A. M. Hofmann (La Jolla, USA) - 2nd edition - U. M. Leuschner (Frankfurt, Germany) ) - 2nd edition - H. Denk (Graz, Austria) - 3rd edition "The current edition contains up-to-date information, but also stands for tradition and progress in hepatology. The reader is carefully introduced into the subject matter and learns to experience and understand everything to the full extent. It is only possible to impart knowledge and to convey enthusiasm if one has great personal involvement. This certainly applies to the author, Erwin Kuntz." O. Univ. Prof. Dr. Helmut Denk, FRCPath Director of the Institute of Pathology University of Graz (Austria).